(3TQM bGfhf GdYed habG dCMOGK GdJYOjdGJs - (3CMeO YHO GdcQje(B, (3CHh TfHs ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2009)
(3GdfXQjI GdYGeI dbGfhf GdYed , GfYbGOYbO GdYed , BKGQ YbO GdYed GdaQOj , GfJgGA YbO GdYed GdaQOj , CMcGe YbO GdYed GdLeGYj , GdfRGYGJ GdYeGdjI GdLeGYjI(B.s
(3eQGLY U(B.365s
Keywords: (3YbhO GdYeds; (3bGfhf GdYed h GdYeGds